The impact of the Apostolic constitution ‘Veritatis gaudium’ on the concept of Quality in ecclesiastical higher education Institutions - Cinquegrani, Riccardo (Warszawskie Studia Teologiczne, 2020)
The paper analyzes the impact on the concept of Quality attributable to the innovations introduced by the Apostolic constitution Veritatis gaudium. The document offers not only operational indications but outlines the objectives that the academic community is invited to take up. Three distinct levels of challenges are highlighted: the role of academic institutions and the need to innovate learning systems; the relationship between higher education centres and the whole society; interdisciplinarity and multidisciplinarity as levers to support knowledge. The article concludes with an invitation to reflect on how to initiate the profound reform process to which higher education institutions are called by Veritatis Gaudium.